2015
DOI: 10.1159/000430142
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Uncoupling Protein 2 Attenuates Cardiac Hypertrophy Induced by Transverse Aortic Constriction in Mice

Abstract: Background: Uncoupling protein 2 (UCP2) is critical in regulating energy metabolism. Due to the significant change in energy metabolism of myocardium upon pressure overload, we hypothesize that UCP2 could contribute to the etiology of cardiac hypertrophy. Methods: Adult male C57BL/6J mice were subjected to pressure overload by using transverse aortic constriction (TAC), and then received genipin (a UCP2 selective inhibitor; 25 mg/kg/d, ip) or vehicle for three weeks prior to histologic assessment of myocardial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…ATP levels were calculated as μM and expressed on the basis of wet tissue weight. A kit based on luciferin/luciferase assay has also been recently used by other researchers for determination of ATP levels [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…ATP levels were calculated as μM and expressed on the basis of wet tissue weight. A kit based on luciferin/luciferase assay has also been recently used by other researchers for determination of ATP levels [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…In animal model of heart failure induced by pressure overload induced by constriction of the ascending aorta, the expression of UCP2 and UCP3 is downregulated and an increase of ROS generation is enhanced to induce cardiac cell hypertrophy [38, 44]. However this model does not involve FFAs-induced upregulation of UCPs that may protect cell from hypertrophy and dysfunction.…”
Section: General Characteristics Of Ucpsmentioning
confidence: 99%
“…In the mammalian heart, UCP2 is the predominant isoform that expressed in the heart and other tissues . It has been reported that UCP2 plays an important role in myocardial injury and cardiac hypertrophy . Nevertheless, the exact role and mechanism of UCP2 in cardioprotection during I/R remain elusive.…”
Section: Introductionmentioning
confidence: 99%